Haematologic Parameters In Acute Promyelocytic Leukemia Patients Treated With ALL Trans- Retinoic acid - Alaa G. Hussein; Mohammed Sh. Ali; Maha Sh. Hassan; Saad Sh. Mansoor; Ali M. AL- Ameri; Raad J. Muhsin (مجلة كلية الطب, 2007)
Background: Acute Promyelocytic Leukemia (APL) is commonly associated with disseminated intravascular coagulation (DIC) and early correction of coagulopathy is of vital importance. All Trans-Retinoic Acid (ATRA) is considered to be the drug of choice in the treatment of APL. Objective: The work was conducted to 1- Identify patients with APL who show laboratory evidence of DIC. 2- Study the serial changes in haemostatic parameters in APL patients treated with ATRA and to compare their results with those treated with conventional chemotherapy without ATRA. Subjective and methods: In this prospective study (from October 2003 to October 2005), 44 newly diagnosed, untreated APL patients were included. ATRA plus chemotherapy – treated patients were 24 while 17 patients were treated with chemotherapy other than ATRA. For each patient, a full clinical evaluation was done and hematological investigations were accomplished at time of diagnosis and repeated on day 3 and 7 of therapy. Diagnosis of DIC was based on finding a positive D- dimer test with hypofibrinogenaemia with or without pathologically prolonged (PT and/or APTT). Results: In 44 newly diagnosed, untreated APL patients studied, the age range between 6-81 years with a median of 27 years. Male to female ratio was 1.3:1. Before treatment all patients had anemia, thrombocytopenia, and elevated level of D – dimer. DIC was present in all patients at time of diagnosis. All parameters that showed abnormal level at time of diagnosis had returned to normality within one week in ATRA treated group, indicating that DIC has essentially resolved. By contrast, those parameters remained abnormal even on day 7 in the chemotherapy treated group. Indicating that DIC was on going. Conclusion: ATRA therapy in APL patients is associated with rapid improvement of coagulopathy therefore , it is justified to be used from day one of the treatment.